A taxonomic revision of the genus Astragalus L. (Fabaceae) in Zanjan province, Iran and describing a new species - Ali Bagheri; Ali Asghar Maassoumi; Farrokh Ghahremaninejad (تاکسونومی و بیوسیستماتیک, 2011)
Zanjan province in NW Iran, with diverse climatic and topographic conditions includes a considerable part of Astragalus gene pool. From 2007 through 2009, a collection as complete as possible was made in this area by the authors. As a results of this study, we added 41 species to the already 75 known species for this province. Furthermore, 9 new species were described for the area from which one new species (Astragalus fausicola Podlech ex Bagheri, Maassoumi & F. Ghahrem. from sect. Incani DC.) is introduced.